The Moderation Role of Budget Ratcheting: The Relationship Between Fiscal Decentralization and Regional Spending - Jurni Hayati; Tiara Pradani; Dodi Tirtana (Equity: Jurnal Ekonomi, 2023)
This research aims to determine whether there is a relationship between fiscal decentralization and local government public spending in Indonesia. This research also aims to determine how budget ratcheting can strengthen the relationship between fiscal decentralization and local government regional spending in Indonesia. This research is a development of a which was modified by adding a Budget Ratcheting variable as moderation. The method used in this research is quantitative by analyzing data collected from provincial-level regional expenditure budget reports in Indonesia from 2018 to 2022. The research results show a significant influence of Fiscal Decentralization (TKDD) on Regional Expenditures (BD). Still, there is no significant influence of Fiscal Decentralization (TKDD) on Regional Expenditures (BD), which is moderated by the Budget Ratcheting (RB). There is a significant influence of Fiscal Decentralization (TKDD) on Regional Expenditures (BD) after adding control variables (PAD and PL). However, there is a moderating influence of theBudget Ratcheting (RB) in strengthening the influence of Fiscal Decentralization (TKDD) on Regional Expenditures (BD) after the control variables (PAD and PL) remain insignificant, so it can be stated that theBudget Ratcheting has not been able to strengthen the positive relationship between fiscal decentralization and regional spending after adding the control variables (PAD and PL).